Self-assembly of heteroleptic dinuclear metallosupramolecular kites from multivalent ligands via social self-sorting - Benkhäuser, Christian; Lützen, Arne (Beilstein Journal of Organic Chemistry, 2015)
A Tröger's base-derived racemic bis(1,10-phenanthroline) ligand (rac)-1 and a bis(2,2'-bipyridine) ligand with a central 1,3-diethynylbenzene unit 2 were synthesized. Each of these ligands acts as a multivalent entity for the binding of two copper(I) ions. Upon coordination to the metal ions these two ligands undergo selective self-assembly into heteroleptic dinuclear metallosupramolecular kites in a high-fidelity social self-sorting manner as evidenced by NMR spectroscopy and mass spectrometry.
Keywords: metal complexes; multivalency; self-assembly; self-sorting; supramolecular chemistry; Tröger's base